”Sign System” Wisata Puncak Kabun Singgalang Kabupaten Agam Sumatera Barat - Fadhil Rahman; Eliya Pebriyeni (Institut Nalanda, 2023)
West Sumatra is known for its beautiful natural charm with various types of tourism. One of the amazing natural destinations in Agam Regency is Singgalang Mountain Peak. However, the Puncak Kabun Singgalang tourist attraction does not have a Sign system which is an identification, information about attractions and Signs as directions. The Puncak Kabun Singgalang tourist attraction is still included in the category of tourist objects that provide little information to visitors. This fact is proven by the absence of a sign system that provides information regarding directions, location maps, as well as security aspects. Therefore, it is necessary to design a sign system at the Puncak Kabun Singgalang tourist destination that is efficient, attractive, full of information, and able to communicate well, making it easier for visitors to explore the Puncak Kabun Singgalang tourist attraction. In this design using the Glassbox method obtained through observation, interviews and documentation. The analytical method used in the design is SWOT analysis. Strengths owned by tourist attractions, Weaknesses owned by tourist attractions, Opportunities (opportunities) from the existence of these tourist attractions, Threats (threats) to tourist attractions. From the results of the design, the author uses the main media Sign system in the form of Information sign. Supporting media include sign systems in the form of regulatory signs, sign systems in the form of signage, tickets, brochures, mugs, posters and stickers.